Experimental investigation of artificial intelligence applied in MPPT techniques - Krachai, Saidia Della; Stambouli, A. Boudghene; Krachai, M. Della; Bekhti, M. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Nano-satellites are key features for sharing the space data and scientific researches. They embed subsystems that are fed from solar panels and batteries. Power generated from these panels is subject to environmental conditions, most important of them are irradiance and temperature. Optimizing the usage of this power versus environmental variations is a primary task. Synchronous DC-DC buck converter is used to control the power transferred from PV panels to the subsystems while maintaining operation at maximal power.  In this paper, artificial intelligence techniques: neural networks and adaptive neural fuzzy inference systems (ANFIS) are used to accomplish the tracking task. Simulation and experimental results demonstrate their efficiency, robustness and tracking quality.